Efficacy of passive hypothermia and adverse events during transport of asphyxiated newborns according to the severity of hypoxic-ischemic encephalopathy - Nuria Carreras; Miguel Alsina; Ana Alarcon; Gemma Arca-Díaz; Thais Agut; Alfredo García-Alix (Jornal de Pediatria, 2018)
Objective: To determine if the efficacy of passive hypothermia and adverse events during transport are related to the severity of neonatal hypoxic-ischemic encephalopathy. Methods: This was a retrospective study of 67 infants with hypoxic-ischemic encephalopathy, born between April 2009 and December 2013, who were transferred for therapeutic hypothermia and cooled during transport. Results: Fifty-six newborns (84%) were transferred without external sources of heat and 11 (16%) needed an external heat source. The mean temperature at departure was 34.4 ± 1.4 °C and mean transfer time was 3.3 ± 2.0 h. Mean age at arrival was 5.6 ± 2.5 h. Temperature at arrival was between 33 and 35 °C in 41 (61%) infants, between 35 °C and 36.5 °C in 15 (22%) and <33 °C in 11 (16%). Infants with severe hypoxic-ischemic encephalopathy had greater risk of having an admission temperature < 33 °C (OR: 4.5; 95% CI: 1.1–19.3). The severity of hypoxic-ischemic encephalopathy and the umbilical artery pH were independent risk factors for a low temperature on admission (p < 0.05). Adverse events during transfer, mainly hypotension and bleeding from the endotracheal tube, occurred in 14 infants (21%), with no differences between infants with moderate or severe hypoxic-ischemic encephalopathy. Conclusion: The risk of overcooling during transport is greater in newborns with severe hypoxic-ischemic encephalopathy and those with more severe acidosis at birth. The most common adverse events during transport are related to physiological deterioration and bleeding from the endotracheal tube. This observation provides useful information to identify those asphyxiated infants who require closer clinical surveillance during transport. Resumo: Objetivo: Determinar se a eficácia da hipotermia passiva e eventos adversos durante o transporte estão relacionados à gravidade da encefalopatia hipóxico-isquêmica neonatal. Métodos: Estudo retrospectivo de 67 neonatos com encefalopatia hipóxico-isquêmica (nascidos entre abril de 2009 e dezembro de 2013) transferidos para hipotermia terapêutica e resfriados durante o transporte. Resultados: Foram transportados 56 recém-nascidos (84%) sem fontes externas de calor e 11 (16%) precisaram de uma fonte externa de calor. A temperatura média na saída foi 34,4 ± 1,4 °C e o tempo médio de transporte foi 3,3 ± 2,0 horas. A idade média na chegada foi 5,6 ± 2,5 horas. A temperatura na chegada ficou entre 33-35 °C em 41 (61%) neonatos, entre 35°-36,5 °C em 15 (22%) e < 33 °C em 11 (16%). Neonatos com encefalopatia hipóxico-isquêmica grave apresentaram maior risco de temperatura < 33 °C na internação (RC 4,5; IC de 95% 1,1-19,3). A gravidade da encefalopatia hipóxico-isquêmica e o pH da artéria umbilical foram fatores de risco independentes para uma baixa temperatura na internação (p < 0,05). Eventos adversos durante o transporte, principalmente hipotensão e sangramento do tubo endotraqueal, ocorreram em 14 neonatos (21%), sem diferenças entre neonatos com encefalopatia hipóxico-isquêmica moderada ou grave. Conclusão: O risco de super-resfriamento durante o transporte é maior em recém-nascidos com encefalopatia hipóxico-isquêmica grave e naqueles com acidose mais grave no nascimento. Os eventos adversos mais comuns durante o transporte estão relacionados a deterioração fisiológica e sangramento do tubo endotraqueal. Essa observação fornece informações úteis para identificar neonatos asfixiados que exigem maior vigilância clínica durante o transporte. Keywords: Birth asphyxia, Hypoxic-ischemic encephalopathy, Neonatal transport, Therapeutic hypothermia, Passive cooling, Thermogenesis, Palavras-chave: Asfixia no nascimento, Encefalopatia hipóxico-isquêmica, Transporte neonatal, Hipotermia terapêutica, Resfriamento passivo, Termogênese